(untitled) (Historia, 2021)
"Pretoria, thou art a City: I am within Thee." It was with thesewords, we are told, that Bishop Bousfield, first Bishop of Pretoria, crossedthe "Aapjis" River and entered the centre of his See on the 7th January,1879. This was the man whose untiring effort was to establish the Churchof the Province of South Africa, in the Transvaal, a task which called forthe greatest strength of will and who in later years was to be branded as"obstinate" and "autocratic" by some on account of these same characteris-tics, and who was to become one of the "characters" of the early RepublicanTransvaal.The Bishop tells us that he was drawn to the missionary field fromchildhood and his entrance to Caius College, Cambridge, was almostthwarted by this impulse. He did not marry until foreign work seemedquite unlikely, but still feeling the missionary urge, stipulated that hisbride must be willing "to go to the earth’s ends if called". He o ce let itslip out that he was willing to go abroad. Mr. Bullock of the Society forthe Propagation of the Gospel, came to hear of it, and so it was that aftersix happy years as Vicar of Andover, and a few more spent in othe!parishes, he was offered the newly created Pretoria Diocese in the middleof 1876. "I knew as little of Pretoria or the Transvaal as others", he wrotelater, and he declined the appointment "since a distant village ip a DuichRepublic seemed no home for my wife and children."A year later, however, the political status of the Transvaal had changedsubstantially, with the annexation of the Republic by Sir Theophil (? Shep.stone. On the offer being renewed, the Bishop then accepted "ittq insurance office did not so raise my premiums as to render it impossil’>le."Thus it was that after his consecration at St. Paul’s on. the 2nd February,1878, the "Beggar" Bishop sailed from Southampton on August 8th ...a9oar the "Danube".